2018
DOI: 10.3390/ijms19010205
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and Clearance of Stable Superparamagnetic Maghemite Iron Oxide Nanoparticles in Mice Following Intraperitoneal Administration

Abstract: Nanomedicine is an emerging field with great potential in disease theranostics. We generated sterically stabilized superparamagnetic iron oxide nanoparticles (s-SPIONs) with average core diameters of 10 and 25 nm and determined the in vivo biodistribution and clearance profiles. Healthy nude mice underwent an intraperitoneal injection of these s-SPIONs at a dose of 90 mg Fe/kg body weight. Tissue iron biodistribution was monitored by atomic absorption spectroscopy and Prussian blue staining. Histopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 48 publications
6
48
3
Order By: Relevance
“…Brown Norway rats treated with IP administration (up to 3.7 mL/kg) of 10 nm iron oxide nanoparticles showed no remarkable morphological alterations in the spleen, lungs, or liver (Prodan et al, 2013). Moreover, while nude mice receiving IP injection (up to 90 mg Fe/kg body weight) of 10 and 25 nm iron oxide nanoparticles exhibited no sign of tissue injury (Pham et al, 2018), IP administration of iron oxide nanoparticles (20-40 mg/kg) in the size range of <50 nm led to severe hepatic and renal injuries in Kunming mice (Ma et al, 2012). As such, more systematic studies on organ specific bio-accumulation and toxicity of intraperitoneally administered MNPs are required to reach a general consensus on the safety and proper application of magnetically assisted IP chemotherapy.…”
Section: Discussionmentioning
confidence: 94%
“…Brown Norway rats treated with IP administration (up to 3.7 mL/kg) of 10 nm iron oxide nanoparticles showed no remarkable morphological alterations in the spleen, lungs, or liver (Prodan et al, 2013). Moreover, while nude mice receiving IP injection (up to 90 mg Fe/kg body weight) of 10 and 25 nm iron oxide nanoparticles exhibited no sign of tissue injury (Pham et al, 2018), IP administration of iron oxide nanoparticles (20-40 mg/kg) in the size range of <50 nm led to severe hepatic and renal injuries in Kunming mice (Ma et al, 2012). As such, more systematic studies on organ specific bio-accumulation and toxicity of intraperitoneally administered MNPs are required to reach a general consensus on the safety and proper application of magnetically assisted IP chemotherapy.…”
Section: Discussionmentioning
confidence: 94%
“…After 10 days from the exposure we were not able to detect zCo-NPs inside the cells, which could be due to NP dissolution and NP clearance. Whereas relatively little effort has been made to investigate NP removal, it is known that it can be affected by multiple factors, including size, shape, chemical-physical surface characteristics and functionalization, which, in turn, influence the formation of aggregates (strongly bonded NPs) and/or agglomerates (loosely bonded NPs) [41,42]. Pham et al [42] reported that if iron oxide nanoparticles are not stabilized appropriately, the particles may aggregate, impeding or slowing the clearance; these studies are of great interest, in particular when NPs are used as contrast agents.…”
Section: Discussionmentioning
confidence: 99%
“…[79] Iron oxide NPs (10 nm) elicited hepatocyte modifications such as karyomegaly and binucleated cells, as well as inflammation in the periportal region. [67] The toxic effects induced by metallic NPs depend largely on their size. Several papers have examined the effect of metallic NP size on their toxic effects.…”
Section: Sprague Dawley Ratsmentioning
confidence: 99%